EFFECT OF TEMPERATURE AND STORAGE TIME OF TUNA FISH (Euthynnus affinis) ON ORGANOLEPTIC AND SENSORY QUALITY - Riris Roiska; Husnul Khatimah Ramli; Eka Aprianti; Putinur Putinur; Tri Wulandari; M. Aksa Azis (Jurnal Perikanan Unram, 2024)
Tuna Fish was one of the main commodities in Ternate North Maluku. The importance of understanding good handling practice would has an impact on the quality of the fish, therefore this research will discuss the effect of temperature and storage time on the organoleptic and sensory quality of tuna fish. The effect of temperature and storage time on organoleptic and sensory quality determined by visually observing and conducting an organoleptic tuna fish and boil test for sensory values on fish. Organoleptic and sensory test were conducted by 30 panelis and all data analyzed using oneway anova and descriptive for sensory quality. The research results were found that the organoleptic quality of room temperature from 0th hour was significantly different with 12th hour and 24th hour and the organoleptic value at chilling room from 0th and 12th hour was significantly different with 24th hour. Overal the results of the sensory/boiled test at chilling temperature were still suitable for consumption because there was no honeycomb, curd, pasty, blood spots and there was no itchy or smell when eaten. Sensory result at room temperature at 0th hour and 12th hour were still suitable for consumption because there was no honeycomb, curd, pasty, blood spots and also It didn’t itchy or smell when eaten, which is different from the 24th hour, it was smells, itchy and there was a burning sensation on the tongue after consumed.